Three Years In: a Consideration of the Impacts of Canada’s Legalization of Cannabis on Law Enforcement - Boyd, Neil (Canadian journal of criminology and criminal justice, 2023)
In October 2018, Canada legalized recreational cannabis. Key goals of legalization included reducing access by minors and eliminating the illicit market. Now, three years into the legal regime, important public policy questions are beginning to emerge. With police being tasked to enforce the Cannabis Act and associated provincial/territorial legislation, there is a critical need to understand their experiences, including the successes they have had, challenges they have experienced, and issues that remain unresolved. This paper begins to address these issues by presenting results from a qualitative study involving law enforcement personnel who, through their primary roles and responsibilities, have been actively involved in overseeing cannabis enforcement (in supervisory roles) since legalization in October 2018. Three key findings emerged from the analyses, and all were tied to the overarching perception that the illicit cannabis market has persisted since legalization: 1) there is a small but significant pattern of abuse of the medical system of production and distribution, specifically tied to designated grower provisions; 2) there are many challenges associated with halting online sales of illicit cannabis; and 3) the issue of unregulated sales of cannabis from Indigenous reserves remains a "hot button" political issue, in need of resolution.